2019
DOI: 10.1001/jamaoncol.2018.5896
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Watch-and-Wait Strategy for Rectal Cancer in Patients With a Complete Response After Neoadjuvant Therapy

Abstract: The watch-and-wait (WW) strategy aims to spare patients with rectal cancer unnecessary resection. OBJECTIVE To analyze the outcomes of WW among patients with rectal cancer who had a clinical complete response to neoadjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
303
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 410 publications
(352 citation statements)
references
References 21 publications
12
303
7
2
Order By: Relevance
“…At present, only approximately 30% of neoadjuvant patients will achieve clinical or pathologic complete responses to nCR therapy and are candidates for organ preservation. Moreover, these patients have better outcomes in terms of disease-free and overall survival (49). However, success of this approach is hindered by lack of molecular and/or functional assays that predict response to therapy, emphasizing the need for development of personalized models that can predict treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…At present, only approximately 30% of neoadjuvant patients will achieve clinical or pathologic complete responses to nCR therapy and are candidates for organ preservation. Moreover, these patients have better outcomes in terms of disease-free and overall survival (49). However, success of this approach is hindered by lack of molecular and/or functional assays that predict response to therapy, emphasizing the need for development of personalized models that can predict treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 40% of patients may show a complete pathologic response following neoadjuvant chemoradiation 31,32 . Some studies have shown that local recurrence and survival in patients not undergoing surgery with complete clinical response compared to patients undergoing surgery with a pathologic complete response are similar, 32,33 while others have shown decreased survival 34 . An unintended consequence of this neoadjuvant chemoradiation is that some patients may refuse subsequent treatment with surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The unsalvageable local disease rate is 0.2-1% [2,3]. Recently, Smith et al [4] observed distant metastases (DM) in 36% of patients with LR compared with only 1% in patients without LR (p = 0.001). These findings incited a debate about the safety of the omission of immediate surgery in terms of the increased risk of DM.…”
mentioning
confidence: 99%